Women and law in India - Flavia (NEW DELHI OXFORD UNIVERSITY PRESS, 2016)
An omnibus comprising : Law and gender inequality : the politics of women's rights in India / Flavia Agnes -- Enslaved daughters : colonialism, law, and women's rights / Sudhir Chandra -- Hindu women and marriage law : from sacrament to contract / Monmayee Basu.